2011
DOI: 10.1017/s0022215110002677
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular decompression may be an effective treatment for nervus intermedius neuralgia

Abstract: Patients with nervus intermedius neuralgia who do not respond to medical treatment may benefit from microvascular decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Of the case reports advocating MVD, their patients experienced pain relief at longterm follow-up of 1-4 years, although pain recurrence is not known past 4 years, unlike our patients with NVC. 6,10 Ultimately there was no difference in the number of painfree months in those with and without NVC, indicating that patients with NVC do not respond better or worse than those without NVC to surgery.…”
Section: Figmentioning
confidence: 92%
See 1 more Smart Citation
“…Of the case reports advocating MVD, their patients experienced pain relief at longterm follow-up of 1-4 years, although pain recurrence is not known past 4 years, unlike our patients with NVC. 6,10 Ultimately there was no difference in the number of painfree months in those with and without NVC, indicating that patients with NVC do not respond better or worse than those without NVC to surgery.…”
Section: Figmentioning
confidence: 92%
“…6,12,14 In these case reports, MVD of the NI without sectioning was sufficient to produce pain relief. 10,11,17 Anatomically, NVC is most likely to occur proximally near the brainstem. As the NI exits the pontomedullary junction, it is in the form of 1-5 roots and travels through the cerebellopontine angle cistern, adhering to CN VIII.…”
Section: Figmentioning
confidence: 99%
“…Therefore, 18 papers were included in the review. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] All reports directly related to geniculate neuralgia were classified as level 4 evidence, consisting of single case reports or small case series. There were two level 1 systematic reviews, which discussed the medical therapy of neuralgia.…”
Section: Methodsmentioning
confidence: 99%
“…Saers et al 8 reported another patient with geniculate neuralgia for whom medical treatment was unsuccessful. Magnetic resonance imaging showed compression of the nervus intermedius by the anterior inferior cerebellar artery.…”
Section: Surgerymentioning
confidence: 99%
“…This is why early diagnosis, as well as classification of otalgia's initial symptom, is paramount to localize the disease correctly. Patients who present with otalgia also should undergo a thorough evaluation from an otorhinolaryngology specialist to rule out non‐neurologic etiologies before considering surgical treatment for GN (Saers, Han, & de Ru, ).…”
Section: Diagnosis Based On Anatomymentioning
confidence: 99%